Analysis of Rockslide and Engineering Slide via Integration between Rock Mechanical and Geophysical Parameters. Issue 2 (October 2021) - Shang, Y; Hasan, M
Abstract: The measurement of rock mechanical parameters is an essential step to assess rockslide and engineering slide to support the design of any underground project.Traditionally, such parameters are obtained by the number of drilling tests. However, such tests suffer from efficiency in terms of time, cost, and data coverage. In addition, drilling methods need more equipment and cannot be performed in steep topographic areas. Thus, the use of geophysical methods, such as electrical resistivity tomography (ERT), is noninvasive, user friendly, and cost effective. In this work, we introduce a new approach that involves the empirical integration of rock mechanical and geophysical parameters. Our novel approach provides an efficient alternative to the borehole tests for the estimation of rock mechanical parameters, such as the rock mass integrity coefficient ( Kv ). This approach gives insights into the subsurface for the assessment of rockslide and engineering slide. The subsurface is mapped with different types of rock mass, such as crushed, poorly integral, and fresh bedrock or integral rock. This approach reduces a significant number of borehole tests and assesses the rock mass quality with more than 90% accuracy compared with traditional approaches. Our novel approach is applicable in most cases.